Treynor, Sharpe, and Jensen Ratio of Health Sector Companies on The Indonesia Stock Exchange Before and During Covid-19 Pandemic Period - Dewi Tamara; Ashuri Ashuri; Satria Katon Bagaskara; Sulhadi Sulhadi (Syntax Idea, 2021)
This research aims to compare the return and risk in investment at the stock portfolio of Health Sector Companies in period before the COVID-19 pandemic and during the COVID-19 pandemic in Indonesia. This research conducted using quantitative method with descriptive approach with secondary data with samples of the stock of Health Sector Companies listed in the Indonesia Stock Exchange ("IDX") which then formulated into a stock portfolio. The research period used is the period March 2019-Feb 2020 for before COVID19 pandemic, and the period March 2020 - Feb 2021 for during the COVID19 pandemic. The stock portfolio return and risk measurement is measured by Sharpe, Treynor, and Jensen Ratio which then will be statistically tested to see if there are significant differences of ratios between the two conditions.